The Anticancer Activity of Lycium barbarum Polysaccharide by Inhibiting Autophagy in Human Skin Squamous Cell Carcinoma Cells In Vitro and In Vivo - Meihua Zeng; Qingtao Kong; Fang Liu; Jun Chen; Hong Sang (International Journal of Polymer Science, 2019)
Objective. This study is aimed at investigating the effects of Lycium barbarum polysaccharide (LBP) on the proliferation and apoptosis of human cutaneous squamous cell carcinoma A431 cells in vitro and in vivo via its regulation on autophagy. Methods. In vitro experiment: A431 cells were treated with different concentrations of LBP, and cell viability was measured by the CCK8 method. Flow cytometry was used to detect the cell apoptosis rate. The expression of Ki67, PCNA, cl-caspase-3, Bcl-2, and LC3II and the phosphorylation status of JNK and ERK1/2, as well as the effect of SP600125 cotreatment on the expression of autophagy and apoptosis-associated proteins, were determined via Western blot. In vivo experiment: a transplanted tumor model was established by subcutaneous injection of A431 cells to the nude mice. 50 mg/kg LBP was injected into the mice intraperitoneally; the survival rate of mice, volume, and weight of tumor were determined on the 30th day. The expression of Ki67 and MMP-2 proteins was measured by immunohistochemistry. Results. LBP at concentrations of 400 μg/ml and above was significantly cytotoxic to A431 cells, whereas, within the dose range of 50 μg/ml~200 μg/ml, LBP significantly inhibited the expression of Ki67 and PCNA proteins, promoted the expression of cl-caspase-3, inhibited the expression of Bcl-2 protein, downregulated the expression of autophagy marker LC3II, and reduced the phosphorylation of ERK1/2, whereas the level of JNK phosphorylation was upregulated. At the same time, the regulation of Beclin1, LC3II, Bcl-2, and cl-caspase-3 by LBP was effectively reversed by the cotreatment of SP600125. In addition, LBP increased the survival rate of transplanted nude mice, reduced tumor volume and weight, and downregulated the expression of Ki67 and MMP-2. Conclusion. LBP can induce apoptosis of A431 cells by inhibiting autophagy and can inhibit tumor growth in vivo.